Synthesis of Red-Emissive CaV2O6 Nanophoshor via a Water Assisted Solid State Reaction Method. (25th October 2021) - Watanabe, Mizuki; Muto, Masaru; Abe, Yusuke; Kaneko, Tatsuro; Toda, Ayano; Uematsu, Kazuyoshi; Ishigaki, Tadashi; Sato, Mineo; Koide, Junko; Toda, Masako; Kudo, Yoshiaki; Masaki, Takaki; et al.
Abstract : Monoclinic CaV2 O6 (under 100 nm in diameter) phosphor was obtained via a water-assisted solid-state reaction (WASSR) method at 80 °C–120 °C and exhibited red emission at room temperature. The estimated average particle size, ratio of the V 5+ ion (the emission center) in the structure, and optical properties were investigated through scanning electron microscopy, X-ray photoelectron spectroscopy, electron spin resonance spectroscopy, UV–vis spectroscopy, and fluorophotometric analysis. The average size of the particles obtained using the WASSR method was less than 100 nm. Compared with CaV2 O6 obtained using the conventional solid-state reaction method, the amount of V 5+ in CaV2 O6 was 16% higher and the emission intensity was 1.4-fold higher by using the WASSR method.